2017
DOI: 10.1177/0306624x17693865
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual Criminology: The Case of Jewish Criminology

Abstract: Throughout the ages and in most cultures, spiritual and religious thinking have dealt extensively with offending (person against person and person against the Divine), the response to offending, and rehabilitation of offenders. Although modern criminology has generally overlooked that body of knowledge and experience, the study of spirituality and its relation to criminology is currently growing. Frequently, though, it is conducted from the secular scientific perspective, thus reducing spiritual knowledge into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 66 publications
0
29
0
Order By: Relevance
“…Studies have shown that the inmate population typically exhibits many disorders (e.g., anxiety, depression, and impulsiveness) along with risky behaviors at higher rates as compared with in the normative population (Auty et al, 2015;Muirhead & Fortune, 2016). Yoga addresses many of these problems and can therefore serve as both a complementary factor and possibly a positive alternative to the existing rehabilitation programs (Auty et al, 2015;Muirhead & Fortune, 2016;Ronel & Ben Yair, 2018;Wimberly & Xue, 2016).…”
Section: Yoga From the Positive Criminology Perspectivementioning
confidence: 99%
“…Studies have shown that the inmate population typically exhibits many disorders (e.g., anxiety, depression, and impulsiveness) along with risky behaviors at higher rates as compared with in the normative population (Auty et al, 2015;Muirhead & Fortune, 2016). Yoga addresses many of these problems and can therefore serve as both a complementary factor and possibly a positive alternative to the existing rehabilitation programs (Auty et al, 2015;Muirhead & Fortune, 2016;Ronel & Ben Yair, 2018;Wimberly & Xue, 2016).…”
Section: Yoga From the Positive Criminology Perspectivementioning
confidence: 99%
“…However, it is important to acknowledge some of the challenges which relate to defining the key terms of this study. According to Ronel and Yair (2017), religion usually refers to a social institute of beliefs, knowledge, norms, rules, customs, and rites. They further state that "religion in general, and spirituality both represent human faith in the Supreme and a quest for ultimate meaning" (2017, p. 2).…”
Section: Religiosity Religion or Spirituality?mentioning
confidence: 99%
“…Moreover, from the perspective of positive criminology, yoga has had several rehabilitative advantages manifest, inter alia, in the development of interpersonal integration, understanding and interpreting daily occurrences from a spiritual outlook, and embracing humane and prosocial views and norms, all of which may assist offenders through their rehabilitation process (Ronel & Ben Yair, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the inmate population typically exhibits many disorders (e.g., anxiety, depression, impulsiveness) along with risky behaviors at higher rates as compared with in the normative population (Auty et al, 2015; Muirhead & Fortune, 2016). Yoga addresses many of these problems and can, therefore, serve as both a complementary factor and possibly a positive alternative to the existing rehabilitation programs (Auty et al, 2015; Muirhead & Fortune, 2016; Ronel & Ben Yair, 2018; Wimberly & Xue, 2016).…”
Section: Introductionmentioning
confidence: 99%